2019
DOI: 10.1371/journal.pgen.1007730
|View full text |Cite
|
Sign up to set email alerts
|

The telomere bouquet is a hub where meiotic double-strand breaks, synapsis, and stable homolog juxtaposition are coordinated in the zebrafish, Danio rerio

Abstract: Meiosis is a cellular program that generates haploid gametes for sexual reproduction. While chromosome events that contribute to reducing ploidy (homologous chromosome pairing, synapsis, and recombination) are well conserved, their execution varies across species and even between sexes of the same species. The telomere bouquet is a conserved feature of meiosis that was first described nearly a century ago, yet its role is still debated. Here we took advantage of the prominent telomere bouquet in zebrafish, Dan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
209
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(228 citation statements)
references
References 100 publications
(152 reference statements)
18
209
1
Order By: Relevance
“…From the cytogenetic standpoint only, certain repetitive DNA markers, including 5S and 18S rDNA, have been formerly found to be involved in the formation of centric fusions (e.g., [39][40][41]). In the case of rDNAs, this may be possibly linked with the susceptibility of these tandemly repeated clusters to double-stranded DNA breaks, perhaps resulting from (1) a frequent rRNA transcription and thus break-prone R-loop emergence, (2) intermingling of NOR (Nuclear Organizer Region)-bearing chromosomes in the interphase nucleus, or (3) possible association of rDNA-bearing sites during the meiotic prophase I [42][43][44][45][46][47][48]. With a few exceptions, the terminal position of the 18S rDNA loci on chromosomes appears to be a common feature for all Lebiasinidae genera analyzed up to now (i.e., Nannostomus, Pyrrhulina, Lebiasina, and Copeina) ( [19][20][21][22], this study).…”
Section: Discussionmentioning
confidence: 99%
“…From the cytogenetic standpoint only, certain repetitive DNA markers, including 5S and 18S rDNA, have been formerly found to be involved in the formation of centric fusions (e.g., [39][40][41]). In the case of rDNAs, this may be possibly linked with the susceptibility of these tandemly repeated clusters to double-stranded DNA breaks, perhaps resulting from (1) a frequent rRNA transcription and thus break-prone R-loop emergence, (2) intermingling of NOR (Nuclear Organizer Region)-bearing chromosomes in the interphase nucleus, or (3) possible association of rDNA-bearing sites during the meiotic prophase I [42][43][44][45][46][47][48]. With a few exceptions, the terminal position of the 18S rDNA loci on chromosomes appears to be a common feature for all Lebiasinidae genera analyzed up to now (i.e., Nannostomus, Pyrrhulina, Lebiasina, and Copeina) ( [19][20][21][22], this study).…”
Section: Discussionmentioning
confidence: 99%
“…Most chromosomes are subtelomeric and submetacentric, and only two are metacentric [99]. It is only recently that the timing of meiotic progression has been described systematically in males and females [17]. It was found that the formation of a telomere bouquet was a key event of early meiosis in zebrafish.…”
Section: Danio Reriomentioning
confidence: 99%
“…Indeed, DSB formation, homologues pairing and synapsis, all start at, or close to, telomeric ends, when telomeres cluster in leptotene/early zygotene. Thus, there is a dramatic polarisation of DSBs and synapsis at telomeres [17,100]. Synapsis then proceeds from telomeres inward to the rest of the chromosome.…”
Section: Danio Reriomentioning
confidence: 99%
See 1 more Smart Citation
“…Although homologs of RAD21L have been identified in other vertebrate genomes, there is a dearth of studies of this cohesin in vertebrates other than mouse. Zebrafish has emerged as an excellent model to use genetic approaches to study the chromosome events in meiosis [38][39][40][41]. Both sexes produce gametes throughout their lives, thus providing a window to study sexually dimorphic features of female and male meiosis.…”
Section: Introductionmentioning
confidence: 99%